Gambaran Kondisi Lingkungan Pasar Winenet di Kota Bitung Tahun 2019 - Fredrik B.J. Om; Odi Roni Pinontoan; Woodford Baren Joseph (Universitas Sam Ratulangi, 2020)
Background: Market sanitation is an effort to supervise activities that take place in the cleanliness as well as sanitation conditions that do not meet the market conditions sanitation market environment, especially related to the ticket or to transmit an illness. The market that is less concerned in Kepmenkes RI number: 519/Menkes/SK/VI/2008 facilitates bacteria or vector to multiply so as to transmit various diseases. The research aims to describe the environment condition of Winenet Tradisional Market in Bitung City 2019. Method: The research method used is a type of descriptive survey research using an observation approach to find out the environmental conditions in the Winenet market Bitung City. The research was conducted on Winenet Market, Bitung City in September to November 2019 data instruments collected directly by researchers using the check list, among others: observation sheets, paperwork tools, documentation with Univariate anolysis on this research to know the description of the market building, waste disposal, waste channels and drainas, toilets, clean water, sanitation place food sales, control transmission of diseases and vectors, handwashing By calculating the frequency distribution of each variable. Result: Market sanitation assessment refers to the check list referring to the decree of the Minister of Health No. 519 year 2008. The research on each question is given a score of 1 for Yes answers and a 0 score for answers no, with a number of questions as many as 45 questions. The final assessment categories are classified as follows: Answer Ya 36 (â‰¥ 80%): Well, yes answer 29-35 (65%-79%): good enough, answer Yes 28 (â‰¤ 64%): less good. Conclusion: The Conclusion in this study is the observation of the overall environment conditions Winenet market is 72,25%. Results demonstrate overall environmental conditions winenet market is good enough.